Introduction of antimicrobial resistance education in pharmacy curricula in India: Lessons learned and future direction - Vrinda Nampoothiri; Dona Boban; Sangita Sudhir; Anu George; Esmita Charani; Sanjeev Singh (Elsevier, 2024)
Introduction: Insufficient training in antimicrobial resistance (AMR) and antimicrobial stewardship (AMS) in the pharmacy curricula limits pharmacists' participation in AMS activities in India. We explored the potential impact of an AMR curriculum implemented as part of a research project in one of the pharmacy colleges in Kerala, India. Methods: Data were collected using documentary analysis (minutes of meetings and the AMR curriculum developed) and semi-structured qualitative interviews with key informants face-to-face or via the Zoom platform at the participant's convenience. Anonymized interview transcripts were thematically analyzed aided by NVivo 12 software. Results: We interviewed faculty (n = 4), clinical pharmacists (n = 3), and students (n = 6) involved in the design, implementation, and use of the new curriculum. The development and implementation of the new curriculum was conducted through strategically planned and established methodology with equal involvement from the pharmacy college and the research project team. Challenges in this process included a lack of human resources to take classes, time, limited interactions, and motivation of students during the online classes. Despite this, students who attended the classes agreed that the curriculum introduced them to AMS and AMR concepts which helped them during their clinical postings. They agreed that it would be beneficial if a similar curriculum was implemented in other pharmacy colleges. Conclusion: Learnings from this study would be beneficial for other pharmacy colleges to implement a similar AMR curriculum for training pharmacy students to take key roles in AMS, especially in countries like India where postgraduate training for pharmacists remains limited.